2017
DOI: 10.1098/rspa.2017.0038
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent boundary layer under the control of different schemes

Abstract: This work explores experimentally the control of a turbulent boundary layer over a flat plate based on wall perturbation generated by piezo-ceramic actuators. Different schemes are investigated, including the feed-forward, the feedback, and the combined feed-forward and feedback strategies, with a view to suppressing the near-wall high-speed events and hence reducing skin friction drag. While the strategies may achieve a local maximum drag reduction slightly less than their counterpart of the open-loop control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…As a result, the skin friction is substantially reduced (figure 14). Interestingly, these LSSVs change little the turbulent energy dissipation (figure 24b), unlike some other techniques such as the piezo-ceramic-actuator-generated spanwise-travelling wave (Bai et al 2014;Qiao et al 2017) where the enhancement of the dissipation in the near-wall region is one of the keys for DR.…”
Section: Weakened Bursting Eventsmentioning
confidence: 96%
See 2 more Smart Citations
“…As a result, the skin friction is substantially reduced (figure 14). Interestingly, these LSSVs change little the turbulent energy dissipation (figure 24b), unlike some other techniques such as the piezo-ceramic-actuator-generated spanwise-travelling wave (Bai et al 2014;Qiao et al 2017) where the enhancement of the dissipation in the near-wall region is one of the keys for DR.…”
Section: Weakened Bursting Eventsmentioning
confidence: 96%
“…Choi et al 1998;Agostini, Touber & Leschziner 2014) or a spanwise/transverse or streamwise-travelling wave (e.g. Du et al 2002;Quadrio et al 2009;Bai et al 2014;Qiao et al 2017).…”
Section: Weakened Bursting Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is accordingly of quite significant interest to enhance our understanding of the dynamic response of a rough wall TBL to various perturbations with increasing Re. To date, wall suction and injection approaches have had some success in controlling of smooth wall TBLs, particularly at low and moderate Re (see Gad-el Hak & Blackwelder 1989;Myose & Blackwelder 1995;Jacobson & Reynolds 1998;Park & Choi 1999;Rathnasingham & Breuer 2003;Lockerby, Carpenter & Davies 2005;Rebbeck & Choi 2006;Segawa et al 2007;Kametani et al 2015;Bobke, Örlü & Schlatter 2016;Qiao, Zhou & Wu 2017). Antonia et al (1988) quantified the influence of wall suction, applied through a porous wall strip, on a low Reynolds number smooth wall TBL.…”
Section: Introductionmentioning
confidence: 99%
“…They compared the performance of piezoelectric vibration drag reduction under different control methods, and concluded that closed-loop control could save a lot of energy. Then, they studied the drag reduction performance under different closed-loop control methods, and verified the results through wind tunnel experiments [171].…”
Section: B Control Methods Of Piezoelectric Actuator For Drag Reductionmentioning
confidence: 98%